Does Botanical Diversity in Sewage Treatment Reed-Bed Sites Enhance Invertebrate Biodiversity?. (27th July 2011) - Feest, Alan; Merrill, Ian; Aukett, Philippa
Abstract : (1) This study examines the effect of increasing botanical diversity, through reed-bed planting and maintenance regimes, on sewage treatment reed-bed invertebrate biodiversity and the possible enrichment of overall catchment biodiversity. (2) Reed-bed invertebrates were identified as a good indicator group of overall site biodiversity quality and were sampled at a range of sewage treatment reed-bed sites in the same geographical area between May and August 2006 (plus one natural reed-bed control site). Standardised water trapping and pitfall trapping techniques were employed throughout this sampling period. (3) Statistical analysis of the sampling results revealed that the number of plant species recorded was inversely related to terrestrial invertebrate species richness, species conservation value index and biomass within the study sites. For example, the natural reed-bed sampled had the highest botanical diversity but the lowest terrestrial invertebrate species richness. (4) This study has demonstrated that sewage treatment reed-beds support a diverse range of invertebrate species, some of them being of national conservation value. This suggests that sewage treatment reed-beds may be at least as biodiverse as naturally occurring reed-beds and will add to the overall biodiversity and ecohydrology of a catchment whilst saving energy.